THE PRACTICE OF THE TIJANIYYA ORDER AMONG MILLENNIALS: A Study on Spirituality and Its Impact on Social and Religious Life - Dasep Supriatna (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2025)
This study examines the practice of the Tijaniyah Order among millennials, exploring how affiliation with this order shapes their spirituality and influences their social and religious lives. Using Social Identity Theory and a qualitative phenomenological approach through semi-structured interviews, the study examines the formation of spiritual identity and cohesion within the group. Findings indicate that a prominent Tijani identity, fostered through shared practices and a sense of community, profoundly influences millennials' self-concept, guides their social interactions, encourages prosocial behavior, and shapes their broader religious expression, demonstrating significant social impact.